Insulin treatment and clinical outcomes in patients with diabetes and heart failure with preserved ejection fraction. (4th July 2019) - Shen, Li; Rørth, Rasmus; Cosmi, Deborah; Kristensen, Søren Lund; Petrie, Mark C.; Cosmi, Franco; Latini, Roberto; Køber, Lars; Anand, Inder S.; Carson, Peter E.; Granger, Christopher B.; Komajda, Michel; et al.
Abstract: Aims: Insulin causes sodium retention and hypoglycaemia and its use is associated with worse outcomes in heart failure (HF) with reduced ejection fraction. We have investigated whether this is also the case in HF with preserved ejection fraction (HFpEF). Methods and results: We examined the association between diabetes/diabetes treatments and the risk of the primary composite of cardiovascular death or HF hospitalization, as well as other outcomes in adjusted analyses in CHARM‐Preserved (left ventricular ejection fraction ≥ 45%), I‐Preserve and TOPCAT (Americas) pooled. Of 8466 patients, 2653 (31%) had diabetes, including 979 (37%) receiving insulin. Patients receiving insulin were younger, had a higher body mass index, prevalence of ischaemic aetiology, N‐terminal pro‐B‐type natriuretic peptide and use of diuretics, worse New York Heart Association class and signs and symptoms, and worse quality of life and renal function, compared to patients with diabetes not on insulin. Among the 1398 patients with echocardiographic data, insulin use was associated with higher left ventricular end‐diastolic pressure and more diastolic dysfunction than in other participants. The primary outcome occurred at a rate of 6.3 per 100 patient‐years in patients without diabetes, and 10.2 and 17.1 per 100 patient‐years in diabetes patients without and with insulin use, respectively [fully adjusted hazard ratio (aHR) insulin‐treated diabetes vs. other diabetes: 1.41, 95% confidence interval (CI) 1.23–1.63, P  < 0.001]. The adjusted HR is 1.67 (95% CI 1.20–2.32, p  = 0.002) for sudden death (insulin‐treated diabetes vs. other diabetes). Conclusions: Insulin use is associated with poor outcomes in HFpEF. Although we cannot conclude a causal association, the safety of insulin and alternative glucose‐lowering treatments in HF needs to be evaluated in clinical trials.